2014
DOI: 10.1128/jvi.02648-13
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Activation Mechanism of Avian Influenza Virus H9N2 by Furin

Abstract: bAvian influenza virus H9N2 is prevalent in waterfowl and has become endemic in poultry in Asia and the Middle East. H9N2 influenza viruses have served as a reservoir of internal genes for other avian influenza viruses that infect humans, and several cases of human infection by H9N2 influenza viruses have indicated its pandemic potential. Fortunately, an extensive surveillance program enables close monitoring of H9N2 influenza viruses worldwide and has generated a large repository of virus sequences and phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 51 publications
1
70
0
1
Order By: Relevance
“…In this regard, there are also parallels with influenza virus, where peptide insertions upstream of the cleavage site/fusion peptide modulate the fusion activity of H7 influenza viruses (Hamilton et al, 2012; Perdue, 2008). In addition, work on influenza virus HA have shown that glycosylations can have profound effects on cleavage activation, as bulky sugar moieties can create steric hindrance around the cleavage site, restricting access for proteases (Kawaoka et al, 1984; Tse et al, 2014). The role of glycosylations in modulating proteolytic activation of the coronavirus S protein, which is known to be heavily glycosylated, has been relatively unexplored and awaits further investigation.…”
Section: Discussion: Spike (S) Cleavage Motifs As Coronavirus Cellmentioning
confidence: 99%
“…In this regard, there are also parallels with influenza virus, where peptide insertions upstream of the cleavage site/fusion peptide modulate the fusion activity of H7 influenza viruses (Hamilton et al, 2012; Perdue, 2008). In addition, work on influenza virus HA have shown that glycosylations can have profound effects on cleavage activation, as bulky sugar moieties can create steric hindrance around the cleavage site, restricting access for proteases (Kawaoka et al, 1984; Tse et al, 2014). The role of glycosylations in modulating proteolytic activation of the coronavirus S protein, which is known to be heavily glycosylated, has been relatively unexplored and awaits further investigation.…”
Section: Discussion: Spike (S) Cleavage Motifs As Coronavirus Cellmentioning
confidence: 99%
“…The hindrance could also be overcome by the addition of multiple basic amino acids to the cleavage site (11)(12)(13). A recent study showed a similar effect of the oligosaccharide on HA cleavage in an H9 LP avian IAV (14). The H9 HA contained an R-S-K-R cleavage motif, which was not cleavable by furin-like ubiquitous proteases when the oligosaccharide was present at the stalk region but became cleavable by these proteases when the oligosaccharide was removed (14).…”
mentioning
confidence: 84%
“…In recent years, there have been increasing concerns regarding virus transmission from birds to humans with the low pathogenic H9N2 AIV being implicated in sporadic outbreaks in Europe and Asia [5]. The H9N2 subtype that displays differences in the levels of pathogenicity [6], remains endemic in Asia and the Middle East [7].…”
Section: Introductionmentioning
confidence: 99%